2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9013344
|View full text |Cite
|
Sign up to set email alerts
|

Sum-Rate Maximization of Uplink Rate Splitting Multiple Access (RSMA) Communication

Abstract: In this paper, the problem of maximizing the wireless users' sum-rate for uplink rate splitting multiple access (RSMA) communications is studied. In the considered model, each user transmits a superposition of two messages to a base station (BS) with separate transmit power and the BS uses a successive decoding technique to decode the received messages. To maximize each user's transmission rate, the users must adjust their transmit power and the BS must determine the decoding order of the messages transmitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…While the decoding orders (ii) and (iii) achieve the same results of U-NOMA with U U,1 → U U,2 and U U,2 → U U,1 , respectively [48], is has been shown that (i) represents the optimal decoding order of RSMA [49]. Thus, in the SIC process, the receiver first attempts to decode a (virtual) user while regarding all the remaining messages as noise.…”
Section: B Urllc 1) U-omamentioning
confidence: 91%
See 1 more Smart Citation
“…While the decoding orders (ii) and (iii) achieve the same results of U-NOMA with U U,1 → U U,2 and U U,2 → U U,1 , respectively [48], is has been shown that (i) represents the optimal decoding order of RSMA [49]. Thus, in the SIC process, the receiver first attempts to decode a (virtual) user while regarding all the remaining messages as noise.…”
Section: B Urllc 1) U-omamentioning
confidence: 91%
“…Recently, several works studied different RSMA implementations in downlink wireless networks [20]- [24], showing that RSMA can improve downlink rate and quality of service, achieving better performance than both NOMA and SDMA. For uplink RSMA systems, authors from [25], [26] study the problem of maximizing the sum-rate under proportional rate constraints for all users, by setting users transmission power and optimizing the decoding order at the BS through exhaustive search. As a result, they show that RSMA achieves better performance than NOMA and OMA techniques, such as frequency division multiple access (FDMA) and time division multiple access (TDMA).…”
Section: A Related Workmentioning
confidence: 99%
“…In [109], RSMA-based C-RAN is realized using several gBSs and aBSs, whereas, the authors of [110] reported the energy efficiency of an RSMA-based gBS towards aerial users. Finally, [111], [112] investigated the downlink and uplink SISO RSMA parameters optimization, supporting that their results would serve as a benchmark for the MIMO system. A summary of RSMA related work is presented in Table V. RSMA is more robust and achieves significantly higher throughput than SDMA and NOMA with and without QoS constraints in the considered imperfect CSIT settings.…”
Section: A Backgroundmentioning
confidence: 96%
“…For multiple users, RSMA realizes up to 15.6% and 21.5% sum rate gains compared to NOMA and OFDMA, respectively, given one SIC layer only for RSMA and NOMA. [112] Multi-user SISO uplink. Max.…”
Section: Max Wsr + Approxmentioning
confidence: 99%
“…Their simulation results shown better performance compared to the baseline schemes. Moreover, the authors of References [28,29] have also provided the rate and power allocation optimization for downlink and uplink transmission in rate splitting multiple access (RSMA) based wireless networks.…”
Section: Related Workmentioning
confidence: 99%